2001
DOI: 10.1110/ps.12901
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic contributions to protein–protein interactions: Fast energetic filters for docking and their physical basis

Abstract: The methods of continuum electrostatics are used to calculate the binding free energies of a set of proteinprotein complexes including experimentally determined structures as well as other orientations generated by a fast docking algorithm. In the native structures, charged groups that are deeply buried were often found to favor complex formation (relative to isosteric nonpolar groups), whereas in nonnative complexes generated by a geometric docking algorithm, they were equally likely to be stabilizing as dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(62 citation statements)
references
References 65 publications
(131 reference statements)
4
53
0
5
Order By: Relevance
“…1 and Tables 1 and 2 are obtained. Thus, solvent inaccessible intermolecular hydrogen bonds appear to be one of the key interactions that distinguishes native from non-native protein-protein complexes and this inference is in good agreement with at least one previous docking study [7].…”
Section: Testing the New Function: Binding Free Energy Surfaces Calcusupporting
confidence: 89%
“…1 and Tables 1 and 2 are obtained. Thus, solvent inaccessible intermolecular hydrogen bonds appear to be one of the key interactions that distinguishes native from non-native protein-protein complexes and this inference is in good agreement with at least one previous docking study [7].…”
Section: Testing the New Function: Binding Free Energy Surfaces Calcusupporting
confidence: 89%
“…Electrostatic interactions also play an important role in determining thermodynamics of binding; i.e., binding affinity (Novotny and Sharp, 1992;Fersht, 1993, 1995;Zhu and Karlin, 1996;Chong et al, 1998;Sheinerman et al, 2000;Norel et al, 2001;Rauch et al, 2002). Substrate binding allows the formation of (potentially) favorable charge-charge interactions between the substrate and target, as well as stabilizing specific salt-bridges and hydrogen bonds Fersht, 1993, 1995;Chong et al, 1998).…”
Section: Iib Biomolecule-ligand and -Biomolecule Interactionsmentioning
confidence: 99%
“…We found that the domain interfaces of IGF-1RΔβ (model) are comparable in computed buried surface area to their respective partners in IRΔβ (cryst) and that their respective shape complementarity parameter 26 S c is also acceptable (data not shown). We have also computed the buried charge κ score, 27 which provides a qualitative estimate of the electrostatic complementarity of the interaction interface between the two proteins-interfaces with unfavorable electrostatic complementarity are characterized by a negative κ score. The interface between the L1 domain of one monomer and the FnIII-2 and FnIII-3 domains of the other monomer in IRΔβ (cryst) has a κ score of 0, whereas in the model of IGF-1RΔβ (model) , the κ score is 2.5 for this interface.…”
Section: Atomic Model Of Igf-1rδβmentioning
confidence: 99%